Cops, cameras, and crisis: the potential and the perils of police body-worn cameras - White, Michael D. (New York University Press, 2020)
Setting the stage: innovation, the current crisis, and police body-worn cameras -- Are BWCs a "silver bullet" solution? Research on the benefits of the technology -- The challenges and limitations of BWCs -- Understanding BWC adoption: past, present, and future -- Charting a course for body-worn cameras in the twenty-first century.